Evaluation of the Soccer Achievement Development Program at PERSIK Kendal - Prawira, Rangga Guntur; Sulaiman, Sulaiman; Pramono, Harry (Department of Physical Education, Sport, Health and Recreation, 2022)
The purpose of this study was to evaluate the results of the soccer sports achievement coaching program in terms of context, input, process and product. The indicators studied were finance, organization, coaching, facilities and infrastructure, human resources and training program. This research is an evaluation research using the CIPP method using a qualitative approach. The population of this study are administrators, coaches, and soccer athletes at PERSIK Kendal. Data collection techniques are observation, interviews, documentation and data triangulation. The data obtained were analyzed qualitatively with the following steps: (1) data reduction, (2) data presentation and (3) drawing conclusions. The results of this study (financial target funds are clear, structured organization, coaching exists but is less organized, adequate and proper facilities and infrastructure are not owned by themselves, Human resources are good, the training program is going well) : (1) Context. (2) input financial. (3) Process. (4) Products. Evaluation of coaching using the CIPP method at PERSIK Kendal can be seen that the expected target is not achieved from the achievement coaching program at PERSIK Kendal.